Hepatotoxic effects of inhalation exposure to polycyclic aromatic hydrocarbons on lipid metabolism of C57BL/6 mice. (January 2020) - Li, Fang; Xiang, Binbin; Jin, Yan; Li, Chao; Ren, Songlei; Wu, Yongning; Li, Jingguang; Luo, Qian
Abstract: Inhalation from ambient air and cigarette smoke is a common route of human exposure to polycyclic aromatic hydrocarbons (PAHs). Little information is available regarding hepatotoxicities of inhaled PAHs so for. In this study, we evaluated the toxic effects of intratracheally instilled benzo[ a ]pyrene (B[ a ]P) on hepatic lipid metabolism of C57BL/6 mice at relevant environmental exposure levels by using two different mass-based lipidomics approaches. The results of mass spectrometry imaging analysis showed that both the abundance and spatial distribution of several lysophosphatidylcholine (LysoPC), phosphatidylcholine (PC) and sphingomyelin (SM) in the liver section were different and changed after inhalation exposure to B[ a ]P. Liquid chromatography coupled with mass spectrometry-based lipidomics analysis and multivariate statistical analysis found that B[ a ]P exposure markedly altered glycerophospholipids, glycerolipids, and fatty acid metabolism in the mouse liver, with increasing of triacylglycerol (TG), phosphatidylinositol (PI) and PC, and decreasing of LysoPCs phosphatidylethanolamines (PEs), lysophosphatidylethanolamine (LysoPEs), free fatty acids (FFAs) and eicosanoids. B[ a ]P-induced lipid metabolic disorders showed a time-dependent effect, which generated three response trajectories with different change trends. Consequently, B[ a ]P exposure induced alteration of hepatic lipids by promoting the uptake from blood or the biosynthesis and transformation in the liver, might contribute to non-alcoholic fatty liver disease, hepatocyte membrane injury, inflammation, and signal system disturbance. Graphical abstract: Unlabelled Image Highlights: Assessing hepatic lipid metabolism disorders induced by PAHs inhalation exposure. Integrating LC-MS and MALDI-IMS approach to analyze lipids in C57BL/6 mice liver. B[ a ]P exposure changed the components and distribution of lipids in liver section. B[ a ]P dysregulated glycerolipids, glycerophospholipids and fatty acid metabolism. B[ a ]P-induced lipid metabolic disorders showed a time-dependent effect.